2003
DOI: 10.1002/jmv.10553
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus protein‐specific IgM, IgA, and IgG subclass responses during the acute and convalescent phase of infection

Abstract: The availability of new generation serological assays allowed re-evaluation of the antibody response to measles virus. IgM, IgA, total IgG, and IgG subclass responses were studied to the three major immunogenic measles virus proteins: the fusion protein (F), haemagglutinin (H), and nucleoprotein (N). Plasma samples were obtained from clinically diagnosed measles cases (n = 146) in Khartoum (Sudan) within a week after onset of the rash. Convalescent phase samples were collected from 32 of 117 laboratory-confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 29 publications
3
25
0
1
Order By: Relevance
“…Почему же тогда у маленьких детей, несмотря на большое количество В1-лимфоцитов, в кро-ви определяются буквально следы IgA? По-видимому, это связано с тем, что плазматические клетки, производные от В1-лимфоцитов, распо-ложены в основном в слизистых и синтезируют львиную долю секреторных IgA [12] [8,11], IgG2-антитела стимулируются углеводными антигена-ми [17], тогда как IgG4, наиболее вероятно, игра-ют важную роль при хронической антигенной стимуляции [18,19]. Однако все не так просто.…”
Section: Discussionunclassified
“…Почему же тогда у маленьких детей, несмотря на большое количество В1-лимфоцитов, в кро-ви определяются буквально следы IgA? По-видимому, это связано с тем, что плазматические клетки, производные от В1-лимфоцитов, распо-ложены в основном в слизистых и синтезируют львиную долю секреторных IgA [12] [8,11], IgG2-антитела стимулируются углеводными антигена-ми [17], тогда как IgG4, наиболее вероятно, игра-ют важную роль при хронической антигенной стимуляции [18,19]. Однако все не так просто.…”
Section: Discussionunclassified
“…Also rise of serum IgM antibody is a biological reaction due to infections (25)(26)(27), the sensitivity and specificity of difference of immunochromatography and had been estimated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available EIA kits were used to detect serum antibodies against measles (25)(26)(27). Using serum and extract liquid residual by using real-time RT-PCR and antibody measurement conducted.…”
Section: Evaluation Of the Diagnostic Reagent Using Clinical Samplesmentioning
confidence: 99%
“…It has recently been shown that most of the neutralization activity in serum is caused by IgG1 and IgG3 with little contribution from IgG2 and IgG4. 37,38 However, there are examples of neutralizing activity of sIgA efficiently inhibiting epithelial colonization and invasion of pathogens through microbial agglutination and virus neutralization. 20 Furthermore, the effect of polymeric IgA and SIgA is superior in comparison with monomeric antibodies.…”
Section: Discussionmentioning
confidence: 99%